Evaluation of iron-folic acid supplementation in young women in Mataram City - Kantari, Eka Suci; Huriyati, Emy; Penggalih, Mirza Hapsari Sakti Titis (Universitas Gadjah Mada, 2022)
Purpose: The government program to prevent iron deficiency anemia in adolescent girls provides iron-folic acid supplementation, usually known as TTD or